Proximal versus distal bone transport for the management of large segmental tibial defect: a clinical case series - Yao Lu; Qian Wang; Cheng Ren; Ming Li; Zhong Li; Kun Zhang; Qiang Huang; Teng Ma (Scientific Reports, 2023)
Abstract This retrospective study compared proximal bone transport and distal bone transport in a series of cases diagnosed with large segmental tibial defects. Patients with a tibial segmental defect (> 5 cm) were eligible for inclusion. Twenty-nine patients were treated using proximal bone transport technique (PBT group) and 21 cases were managed by distal bone transport technique (DBT group). We recorded the demographic information, operation indexes, external fixation index (EFI), visual analog score (VAS), limb function scores, and complications. Patients were followed for 24–52 months. There was no significant difference in operation time, blood loss, time in frame, EFI and HSS score between the two groups (p > 0.05). However, the PBT group displayed better clinical effects than the DBT group, including higher AOFAS scores, lower VAS, and complication incidence (p < 0.05). In particular, the incidence of Grade-II pin-tract infection, transient loss of ankle movement, and foot drop was significantly lower in PBT group than that in DBT group (p < 0.05). Although both methods could be used safely for the management of large segmental tibial defects, the proximal bone transport may confer greater patient satisfaction because of better ankle functions and lower complications.